MERS-CoV vaccine candidates in development: The current landscape. Issue 26 (3rd June 2016) - Modjarrad, Kayvon
Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV), an emerging infectious disease of growing global importance, has caused severe acute respiratory disease in more than 1600 people, resulting in more than 600 deaths. The high case fatality rate, growing geographic distribution and vaguely defined epidemiology of MERS-CoV have created an urgent need for effective public health countermeasures, paramount of which is an effective means of prevention through a vaccine or antibody prophylaxis. Despite the relatively few number of cases to-date, research and development of MERS-CoV vaccine candidates is advancing quickly. This review surveys the landscape of these efforts across multiple groups in academia, government and industry.